Issues in the measurement and construction of the consumer price index in Pakistan - Malik, Sohail Jehangir; Nazli, Hina; Mehmood, Amina; Shahzad, Asma (International Food Policy Research Institute, 2014)
The Consumer Price Index (CPI) is one of the most important measures used in economic analysis. The more common uses are: the indexation of wages, rents, contracts and social security payments; the deflation of household consumption in the national accounts; and as a general macroeconomic indicator, especially for inflation targeting and for setting interest rates. Elements of a CPI are also often used in the calculation of purchasing power parities (PPPs) required in the Interna-tional Comparison Program (ICP) (UN, 2009). As such it also has very significant political implications when the performance of the governments is assessed in terms of real growth, inflation and poverty reduction.